HYDROGEN PEROXIDE OF HONEY ANTIBACTERIAL EFFECT AGAINST COAGULATES-NEGATIVE STAPHYLOCOCCI - Rana; A. Faaz (Basrah Journal of Veterinary Research)
ABSTRACT The aim of this study was to determine the minimum active dilution of two standardized type, representative honeys from two bees farm for 7 clinical isolates of coagulates-negative staphylococci. An agar incorporation technique was used to determine the minimum active dilution, with dilution steps for 1% (v/v) honey and 5% (v/v) for sugar syrup .The plates were inoculated with 10 µL spots of cultures of the isolates. the pasture honey inhibited at mean SD3.2± 0.7% (v/v),3.3 ± 0.5% (v/v) for the Manuk honey and 30.9 ± 1.9% (v/v) for the sugar syrup. Typical honeys are about eight times more potent against coagulase-negative staphylococci than bacterial inhibition were due to their osmolarity alone, but also the activity of honey by having its content